PO.16 Is quinine useful in muscle cramps? A Cochrane meta-analysis. Issue 9 (7th August 2011) - El-Tawil, S; Valli, H; Al Musa, T; Lunn, M P T; Weber, M
Abstract : Background: Global controversy on the efficacy and safety of quinine for muscle cramps (banned in USA, widely prescribed in UK), led us to conduct a meta-analysis of all trials comparing quinine to placebo or other treatments. Methods: We searched The Cochrane Register of Controlled Trials, MEDLINE, and EMBASE up to July 2010. Inclusion Criteria: randomised controlled trials, cramps in any location and of any cause. Primary outcome: cramp frequency. Secondary outcomes: cramp intensity, duration, cramp days, adverse events. Results: 23 randomised trials with a total of 1586 participants were included. Quinine was compared to placebo (20 trials), vitamin E (4 trials), a quinine-vitamin E combination (3 trials), and a quinine-theophylline combination (1 trial). The most commonly-used quinine dosage was 300 mg/day. Compared to placebo, quinine significantly reduced cramp number by 28%, cramp intensity by 10%, and cramp days by 20%. Cramp duration was not significantly affected. The other treatment comparisons were not significantly different to quinine. There were significantly more minor adverse events with quinine than placebo (risk difference, RD +3%), mainly gastrointestinal symptoms, but no difference in major adverse events (RD 0%). Conclusion: There is moderate quality evidence that quinine significantly reduces cramp frequency, intensity and cramp days. With use up to 60 days, the incidence of serious adverse events is not significantly greater than placebo.